2022
DOI: 10.1117/1.jmm.21.4.041402
|View full text |Cite
|
Sign up to set email alerts
|

Review of metal-containing resists in electron beam lithography: perspectives for extreme ultraviolet patterning

Abstract: Background: Metal-containing resists entered the mainstream semiconductor industry process flow to mitigate the low absorbance of extreme ultraviolet (EUV) radiation by thin films of organic resists that lead to poor sensitivity and their inability to handle rigors of development and etching conditions.Aim: The long and rich history of using metal-containing resists in electron beam lithography can offer interesting lessons, pointers, and insights to the relatively newcomer EUV lithography, which is slightly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 207 publications
0
19
0
Order By: Relevance
“…21−26,30−48 While the market of semiconductor industries is skyrocketing, the need for resist compositions for low-cost and efficient patterning of advanced node device architecture, particularly nanopatterning at a single nanometer regime, is quite evident. 3,4 Owing to their importance in specialized applications, the cells of memory devices need complex metal interconnect features. 49 It is to be noted that the fabrication of advanced CMOS devices involves complex processes, wide-ranging advanced materials, and technologies, particularly considering current trends and market demand.…”
Section: ■ Introductionmentioning
confidence: 99%
“…21−26,30−48 While the market of semiconductor industries is skyrocketing, the need for resist compositions for low-cost and efficient patterning of advanced node device architecture, particularly nanopatterning at a single nanometer regime, is quite evident. 3,4 Owing to their importance in specialized applications, the cells of memory devices need complex metal interconnect features. 49 It is to be noted that the fabrication of advanced CMOS devices involves complex processes, wide-ranging advanced materials, and technologies, particularly considering current trends and market demand.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17 Different molecular negative resists have been published that show good performance. 18 Tin-oxo cages are known to work as negative tone photoresists under EUV exposure and in EBL.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen silsesquioxane is an inorganic negative resist and has shown an excellent resolution of 7 nm lines at 30 nm pitch obtained with an exposure dose of 7000 pC/cm at 30 KV . Different molecular negative resists have been published that show good performance . Tin-oxo cages are known to work as negative tone photoresists under EUV exposure and in EBL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, patterning on silicon nitride membranes, although good for the demonstration of resolution, severely limits the practical use of materials. It has been long observed that removing the lift-off and etching steps is crucial to achieving sub 10 nm resolution in the direct patterning of functional materials using conventional electron beam lithography. By circumventing these lithographic steps and using a low-molecular-mass single-source precursor resist, we demonstrated patterning of features whose width is close to the probe diameter. We speculate that the use of single-source precursor resists of high atom economy coupled with improvements in the electron–optical column of conventional electron beam lithography machines incorporating spherical aberration correctors would make direct patterning of functional materials at an angstrom scale on silicon substrates a distinct possibility.…”
mentioning
confidence: 99%